Practice, Knowledge, and Barriers for Screening of Hepatocellular Carcinoma Among High-Risk Chinese Patients - Kerui Xu; Shinobu Watanabe-Galloway; Fedja A. Rochling; Jianjun Zhang; Paraskevi A. Farazi; Hongyan Peng; Hongmei Wang; Jiangtao Luo (Ubiquity Press, 2017)
Background: Hepatocellular carcinoma (HCC) is among the leading causes of cancer deaths in China. Considering its poor prognosis when diagnosed late, Chinese guidelines recommend biannual screening for HCC with abdominal ultrasound and serum α-fetoprotein (AFP) test for high-risk populations. Objectives: To investigate the practice, knowledge, and self-perceived barriers for HCC screening among high-risk hospital patients in China. Methods: An interview-based questionnaire was conducted among Chinese patients with chronic hepatitis B and/or chronic hepatitis C infection from outpatient clinics at 2 tertiary medical institutions in Shanghai and Wuhan, China. Findings: Among 352 participating patients, 50.0% had routine screening, 23.3% had irregular screening, and 26.7% had incomplete or no screening. Significant determinants for screening included higher level of education, underlying liver cirrhosis, a family history of HCC, and better knowledge concerning viral hepatitis, HCC, and HCC screening guidelines. Moreover, factors associated with better knowledge were younger age, female gender, urban residency, education level of college or above, annual household income of greater than 150,000 RMB, and longer duration of hepatitis infection. The 3 most common barriers reported for not receiving screening were not aware that screening for HCC exists (41.5%), no symptoms or discomfort (38.3%), and lack of recommendation from physicians (31.9%). Conlusions: Health care professionals and community leaders should actively inform patients regarding the benefits of HCC screening through design of educational programs. Such interventions are expected to increase knowledge about HCC and HCC screening, as well as improve screening adherence and earlier diagnosis.